RENDAHNYA KEMAMPUAN NUMERASI SISWA SEKOLAH DASAR DI SEKOLAH PENGGERAK - Heny Susilowati; Azamul fadhly Muhammad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the low numeracy skills of students in Elementary Schools implementing the Sekolah Penggerak program. The results of the analysis show that 62% of students are in the moderate numeracy ability category, while 8% of students are classified as very low. The data also revealed that 87% of students were unable to perform division operations, 48% were unable to multiply, 38% were unable to subtract, and 17% were unable to add. These findings indicate a significant gap in the understanding of basic numeracy concepts among students, which can have a negative impact on their academic achievement. The data collection method in this study used a mixed method approach. Quantitative data were obtained through a specially designed numeracy ability test, consisting of 20 multiple-choice questions covering basic mathematical operations. Qualitative data were collected through in-depth interviews with 10 teachers and 10 parents of students, which aimed to explore their views on factors that influence students' numeracy skills. Quantitative data analysis was carried out using descriptive statistics, while qualitative data were analyzed using thematic analysis. This study recommends the need to develop more effective learning strategies and increase collaboration between schools and parents to support the development of students' numeracy skills